GAS DISPERSION MODELLING USING CELLULAR AUTOMATA METHOD - SONDA (NIM: 20115048), ATIA
The process of releasing gas can be found in the oil and gas industry. In the oil and gas company, for maintenance purpose, the transmission pipeline need to be replaced with the new one. For safety reason, the gas inside the pipeline need to be emptied by venting process. The gases that emitted during venting process may cause fire or explosion and may cause negative impact to the environment. Once gasses emitted to ambient air, it would not possible to control. Today, the method known as Cellular Automata (CA) has been developed as an approach to model various natural phenomena including the phenomenon of gas dispersion. CA is a discrete dynamic system with area, time and the system used are discrete variables. The area of observation on CA consists of a grid of cells. The state of the cell will be updated each time with certain rules so it can describe the process of gas dispersion. The study of dispersion model from venting process is intended to predict the gas concentration in ambient air and to predict safe area radius to avoid the explosion during venting process.